Navigating the Intersection of Agribusiness and Agri-Entrepreneurship: Performance, Challenges, and Opportunities - Jyoti, Seema Rani; Khushbu; Anju (Archives of Current Research International, 2024)
Agripreneurship, the integration of entrepreneurial principles into agriculture, has become a vital strategy to boost the profitability and attractiveness of farming. This study evaluates the performance of agripreneurs in Haryana, India, focusing on various indicators of success including capacity utilization, cost-benefit ratio, hired labor, perceived profitability, labor relationships, extent of diversification, and social impact. Data was collected from 60 agripreneurs across four districts—Bhiwani, Jind, Hisar, and Kurukshetra—using a structured interview schedule. The results reveal that a significant portion of agripreneurs (46.67%) utilized their capacity to a large extent, while 60% perceived their enterprises as profitable. The findings also indicate that 50% of the businesses had a high level of social contribution and most agripreneurs demonstrated medium to high levels of innovativeness. Statistical analysis shows positive significant relationships between various independent variables (such as age, education, income from agribusiness, risk orientation, and experience) and agribusiness performance. The study concludes that agripreneurs exhibit a high degree of capacity utilization and profitability, maintain generally good labor relationships, and contribute significantly to their communities. The data supports the assertion that both personal and external factors play crucial roles in the success of agribusiness ventures.